THE EVOLVING LANDSCAPE OF INVESTOR PROTECTION: BALANCING STATE SOVEREIGNTY AND INVESTOR RIGHTS IN THE 21ST CENTURY - Rahmonov, Jaloliddin (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The evolving landscape of investor protection in the 21st century requires a delicate balance between safeguarding investor rights and preserving state sovereignty. As global investments expand, investors seek legal assurances to protect their assets, while states must retain the ability to regulate in the public interest, addressing economic, social, and environmental challenges. This tension has sparked debates about the role of investor-state dispute settlement (ISDS) mechanisms and the need for reform. By modernizing investment treaties and dispute resolution processes, the international community can create a more equitable system that fosters both investment and sustainable development, ensuring mutual benefits for investors and states alike.